Influence of Primary Somatosensory Cortex on Interhemispheric Inhibition - Zapallow, Christopher M. (My University, 2013)
The control of unimanual and bimanual tasks is a highly orchestrated process in which primary motor cortex (M1) and primary somatosensory cortex (SI) play key roles. While somatic cortices are known to aid in the control of hand movements, the neural mechanisms by which they act remain largely unknown. One mechanism which is thought to mediate the control of hand movements between bilateral M1s is called interhemispheric inhibition (IHI), a neurophysiological mechanism by which one M1 is able to inhibit the contralateral M1, reducing the occurrence of unwanted movements, or enabling the performance of two differing tasks. Previous research suggests that IHI may be one mechanism by which SI aids in the control of hand movements and this thesis further examined this relationship. Two experiments were performed to investigate the influence of SI on IHI. Experiment 1 investigated the effects of direct modulation of SI cortical excitability on IHI. Experiment 2 investigated the effects of peripheral somatosensory inputs on IHI. The collective results of Experiments 1 and 2 suggest that SI can indeed modulate IHI from either the cortical or peripheral level, with increases in IHI seen following either intervention. Further, it was found that SI selectively modulates only the short latency phase of IHI (SIHI) as well as that mixed afferent inputs were most effective in altering SIHI. The novel findings of this thesis suggest that SI is indeed capable of aiding in the control of motor outputs and thus may be a possible target in future rehabilitative strategies.
Keywords: Primary somatosensory cortex; SI; interhemispheric inhibition; IHI; cTBS; peripheral somatosensory input; Motor Control; Motor Control